Effects of the Continuity of Daily Life Record Chart and of Voluntary Training in Elderly People with Mild Care - Hashimoto, Takayuki; Mimura, Kanichi; Kawabata, Takashi (European Journal of Applied Sciences, 2023)
21 elderly people receiving light nursing care were asked to fill in daily life record charts and to do voluntary training for three months. They were then divided into two groups, in order to assess the effects of the above activities: the “completion” group, who were able to continue the program during the 3-month period, and the “resignation” group, who resigned from the program without finishing the 3-month period. Comparing the two groups of participants, we found that the resignation group showed a significantly lower figures in the duration of home-visit rehabilitation, daily life record chart, voluntary training, HDS-R, and frequency of going out (p<0.05). As for the changes after the intervention, the completion group showed an increase in ROM, MMT, and FIM (p<0.05). The resignation group showed a significant increase only in FIM, but no significant difference in ROM or MMT. As for the achievement of daily life record chart and of voluntary training, the daily life record chart proved to be easier for the participants to work on. It was revealed that those who have been using the in-home rehabilitation service for a long time are more likely to establish the daily life record chart log and voluntary training. These findings suggest that the continuation of daily life record charts and of voluntary training are effective in improving physical functions and in acquiring exercise habits.